1980
DOI: 10.1136/jnnp.43.10.925
|View full text |Cite
|
Sign up to set email alerts
|

Human sensory nerve compound action potential amplitude: variation with sex and finger circumference.

Abstract: In antidromic sensory conduction studies, the nerves were stimulated by saline soaked pads spaced 2-5 cm. apart. A Disa 14E11 constant voltage stimulating unit delivered pulses 0-1 ms in duration. Supramaximal stimuli excited the median and ulnar nerves at the wrist, and the superficial branch of the radial nerve in the lower forearm. The median and ulnar nerve CAPs were recorded with Teca ring electrodes at the index and little fingers, respectively, the recording electrodes being at the level of the proximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 6 publications
4
62
0
1
Order By: Relevance
“…For the sensory parameter, we have demonstrated that gender affects sensory nerve amplitude for the median and ulnar nerves, as was demonstrated by others [3,10]. Arm length has no effect on nerve conduction velocity, in contrast to the influence of leg length and height on nerve conduction study of the leg [14][15][16].…”
Section: Discussionmentioning
confidence: 59%
“…For the sensory parameter, we have demonstrated that gender affects sensory nerve amplitude for the median and ulnar nerves, as was demonstrated by others [3,10]. Arm length has no effect on nerve conduction velocity, in contrast to the influence of leg length and height on nerve conduction study of the leg [14][15][16].…”
Section: Discussionmentioning
confidence: 59%
“…N1 amplitudes of CAP reflects excitability of fast-conducting myelinated axons (Fig. 8), and represents the sum of all individual action potentials (Bolton and Carter, 1980;Velumian et al, 2011). The average N1 amplitudes in CCI animals were significantly reduced compared to responses recorded in sham-operated animals ( p < 0.005; Fig.…”
Section: Corpus Callosum Compound Action Potentials (Cap) Following CCImentioning
confidence: 92%
“…Age and stimulation-to-recording distance were entered as covariates because of their known effects on peripheral nerve sensory action potentials (Bolton & Carter, 1980;Horowitz & Krarup, 1992).…”
Section: Separate 2 Group (Hypertensive Normotensive) Analyses Of Comentioning
confidence: 99%